Furniture in the Ancient World. Origins and Evolution, 3100-475 B.C. With an Introduction by Sir Gordon Russell - Baker, Hollis S. (1966)
US edition 466 fig.; $17.95; espec. Part II (157-232, fig. 246-374): The Near East: 1. Sumer; 2. From the Akkadian Period to the End of the Kassite Period; 3. The Assyrian and Neo-Вabylonian Periods; 4. The Peripheral Regions (Syria, Palestine, Persia, Asia Minor).